Effect of foliar nutrition on productivity and profitability of soyabean under rainfed condition - Anjali Ram Kishor Varma; Abhinandan Singh; Utkarsh Singh; Muyeen I Nargund; Mayank Mani Tripathi (Annals of Agricultural Research, 2024)
A field experiment was carried out on the effect of foliar nutrition on productivity and profitability of soybean under rainfed condition. The experiment was conducted at the Crop Research Centre, School of Agriculture, ITM University Gwalior (M.P.) during the Kharif season of 2022. The experiment was laid out in a randomized block design with 10 treatment combinations and each treatment was replicated thrice, which includes RDF(100%) at the time of sowing, NPK (19:19:19) @ 0.5% at 40 DAS, NPK (19:19:19) @ 1.0% at 40 DAS, NPK (19:19:19) @ 1.5% at 40 DAS, NPK (13:0:45) @ 0.5% at 60 DAS, NPK (13:0:45) @ 1.0% at 60 DAS, NPK (13:0:45) @ 1.5% at 60 DAS, NPK (19:19:19) @ 0.5% at 40 DAS + NPK (13:0:45) @ 0.5% at 60 DAS, NPK (19:19:19) @ 1.5% at 40 DAS + NPK (13:0:45) @1.5 % at 60 DAS and RDF (20:60:20) + Sulphur and one absolute control. The result of the experiment revealed that application of NPK (19:19:19) @ 1.5% at 20 DAS + NPK (13:0:45) @1.5% at 40 DAS recorded the higher grain yield (2153.37 ka ha-1), stover yield (3253.23 ka ha-1) and biological yield (5409.09 ka ha-1). The highest gross return (100287.9 Rs ha-1), net return (70560.78 Rs ha-1), and B:C ratio (2.37) were recorded with the application of NPK (19:19:19) @ 1.5% at 20 DAS + NPK (13:0:45) @1.5% at 40 DAS.